Domestic bond portfolio adjustments during duration jumps - Samuel Donald Achord; Søren Lejsgaard Autrup; Nastasija Loncar; Alexander Meldgaard Otte; Lars Risbjerg; Casper Rønde; Johan Emil Westergaard (Danmarks Nationalbank, 2021)
This Memo investigates the bond portfolio reaction of key Danish institutional investors to duration jumps in callable mortgage bonds. It shows that the investors remain net buyers of Danish mortgage bonds during periods of jumps. In particular, they buy more than they do on average, supporting the Danish mortgage bond market, limiting a potential self-reinforcing mechanism of duration jumps.
Keywords: 330; Monetary policy; Government bonds; Duration; Monetary-policy transmission